PENGARUH PELAYANAN PENDIDIKAN TERHADAP KEPUASAN MAHASISWA JURUSAN KEBIDANAN POLTEKES DEPKES PROVINSI ACEH - Tarmizi Gadeng; Lisa Andriani (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
This aim of this research is to know the influence of serving toward the satisfaction of midwifery department in department of health,  Aceh Province. The sample of this research is 70 students that it’s consisted of the second grade and the third grade of students which is taken randomly. Data collecting was carried out with questionnaires and data analysis with multiple linear regression.The results of research finds that it influence service toword the satisfaction of students of midwifery department in health department of Aceh Province. It’s better for students evaluation toward education service, it’s also higher to their satisfaction to the the department. Based on the results of evaluation statistical is know that F-testF-table, and t-test for each services are also bigger when it’s compared to t-table. So, it can be concluded, either simultan or partial, all dimensions of service quality that influence significant to the student satisfaction of midwifery department in department of health, Aceh Province.Keywords: satisfaction, influence of serving